2020
DOI: 10.1371/journal.pone.0231809
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and demographic vulnerability of adder populations: Results of a genetic study in mainland Britain

Abstract: Genetic factors are often overlooked in conservation planning, despite their importance in small isolated populations. We used mitochondrial and microsatellite markers to investigate population genetics of the adder (Vipera berus) in southern Britain, where numbers are declining. We found no evidence for loss of heterozygosity in any of the populations studied. Genetic diversity was comparable across sites, in line with published levels for mainland Europe. However, further analysis revealed a striking level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 102 publications
1
8
0
Order By: Relevance
“…The absence of sex-biased dispersal at the very local scale could be explained by the strong philopatric behavior in this species outside of reproduction (Madsen and Shine 1992a;Luiselli 1993). The high relatedness pattern observed in mainland Britain confirms the philopatric behavior of the adder (Ball et al 2020). The similar autocorrelation level between sexes at the local scale could also be related to variation among males in reproductive activities, with some individuals moving less for mating or individuals that are just coming back to their birthplace after mating.…”
Section: The Dispersal Is Male-biased and Scale-dependentsupporting
confidence: 53%
See 2 more Smart Citations
“…The absence of sex-biased dispersal at the very local scale could be explained by the strong philopatric behavior in this species outside of reproduction (Madsen and Shine 1992a;Luiselli 1993). The high relatedness pattern observed in mainland Britain confirms the philopatric behavior of the adder (Ball et al 2020). The similar autocorrelation level between sexes at the local scale could also be related to variation among males in reproductive activities, with some individuals moving less for mating or individuals that are just coming back to their birthplace after mating.…”
Section: The Dispersal Is Male-biased and Scale-dependentsupporting
confidence: 53%
“…High genetic diversity is important for the conservation of V. berus populations, as inbreeding within a small isolated population of adders can lead to a strong reduction in population size (Madsen et al 1999(Madsen et al , 2004. Very recently, Ball et al (2020) observed a high relatedness of individuals in small isolated populations, but without loss of genetic diversity at the population level. The fact that higher genetic diversity was observed only in males is intriguing and deserves further work.…”
Section: Effect Of the Environment On Population Structure And Genetic Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn may lead to inbreeding depression, as observed in a small Swedish adder population (Madsen et al 1996(Madsen et al , 2020. However, recent genetic work based on microsatellites suggested that UK adder populations retain surprisingly high levels of heterozygosity, comparable to those from continental European populations (Ball et al 2020). On the other hand, this study also highlighted high levels of relatedness between most individuals within their respective populations.…”
Section: Introductionmentioning
confidence: 50%
“…), particularly the smaller-bodied 'dwarf' members of the genus, are regularly traded on global pet markets (Barlow et al 2012;Auliya et al 2016), but the consequences for wild populations are poorly studied. Although the dispersal ability of B. atropos is unknown, they are likely to have small home ranges and low vagility, similar to other species of dwarf adders (Maritz & Alexander 2012a, 2012bBehrooz et al 2015;Maritz et al 2016;Ball et al 2020).…”
Section: Introductionmentioning
confidence: 72%